TiO2/graphitic carbon nitride nanosheet composite with enhanced sensitivity to atmospheric water - Tosapol Maluangnont; Phieraya Pulphol; Satana Pongampai; Thawanrat Kobkeatthawin; Siwaporn Meejoo Smith; Naratip Vittayakorn (RSC Advances, 2023)
/CNNS composite without complicated curve fitting procedure or dedicated humidity control.
Keywords: Gas Sensing Nanomaterials and Sensors; Ga2O3 and related materials; Analytical Chemistry and Sensors